Foliar Aspersion of Salicylic Acid Improves Nutraceutical Quality and Fruit Yield in Tomato - Oscar Sariñana-Aldaco; Esteban Sánchez-Chávez; Enrique Troyo-Diéguez; Luis Mario Tapia-Vargas; Juan Carlos Díaz-Pérez; Pablo Preciado-Rangel (Agriculture, 2020)
The use of elicitors or biostimulants such as salicylic acid (SA) is an emerging novel practice to improve the yield and quality of crops since it plays an important role in the regulation of various physiological and metabolic processes. The objective of this research was to study the effect of the foliar application of SA on the nutraceutical quality and yield of tomato fruits. A completely randomized experimental design with 10 repetitions was used. SA was applied at five doses (0.025 mM, 0.05 mM, 0.075 mM, 0.1 mM, and 0.125 mM) every 15 days through foliar sprays after transplantation, accumulating seven applications through the cycle. The response variables were yield (total fruit weight per plant), fruit parameters (weight, diameter, firmness, and total soluble solids), percentage of weight loss, and nutraceutical quality. The obtained results suggest that the foliar spraying of SA improves the yield and biosynthesis of phytochemical compounds in tomato fruits, compared to control plants. According to the results, it is advisable to use the dose of 0.125 mM of SA since it has a higher content of bioactive compounds without compromising yield.